The Timing of Preference and Prejudice in Sequential Hiring Games - Glen R. Waddell; Logan M. Lee (Institute for the Study of Labor (IZA), 2014)
We model a hiring process in which the candidate is evaluated sequentially by two agents of the firm who each observe an independent signal of the candidate's productivity. We introduce the potential for taste-based discrimination and characterize how one agent's private valuation of the candidate influences the other agent's hiring practices. This influence is often in an offsetting direction and is partially corrective. Yet, this offsetting response can also be large enough that even a high-productivity candidate who is privately favoured by one agent, as may be the case in efforts to increase gender or racial diversity, is less likely to be hired even when the other agent has no preference over private, non-productive attributes.
Keywords: J1; J7; D8; 330; hiring; race; gender; diversity; discrimination